KIDNEY STONES – WHEN TO USE MINI-PERCUTANEOUS NEPHROLITHOTOMY AND WHEN TO USE ULTRA-MINI PERCUTANEOUS NEPHROLITHOTOMY?: A NARRATIVE REVIEW - Anhelina Loputs,; Anastasiia Holoborodko,; Ewa Wieczorkiewicz,; Eliza Garbacz,; Agnieszka Pocheć,; Bartosz Lautenbach,; Dariusz Nędza,; Klaudia Wojciech,; Patrycja Stępińska,; Wiktoria Błaszczyk, (International Journal of Innovative Technologies in Social Science, 2026)
Background: Miniaturized percutaneous nephrolithotomy techniques have been developed to reduce the morbidity associated with standard percutaneous nephrolithotomy (PCNL) while maintaining high stone clearance. Among these approaches, mini-PCNL and ultra-mini PCNL (UMP) are increasingly used; however, their optimal indications remain incompletely defined.Aims: To review and synthesize current evidence regarding the efficacy, safety, and clinical indications of mini-PCNL and UMP in the management of kidney stone disease.Methods: A narrative review of the literature was performed using PubMed/MEDLINE, Scopus, and Web of Science databases. Clinical studies, comparative analyses, meta-analyses, reviews, and international guideline documents addressing mini-PCNL and UMP were included. Evidence was synthesized descriptively with emphasis on stone- and patient-related factors influencing technique selection.Results: Both mini-PCNL and UMP demonstrated high stone-free rates when applied in appropriately selected patients. Mini-PCNL achieved superior stone clearance for larger (15–30 mm), multiple, or high-density renal stones, owing to efficient fragment extraction. UMP was associated with lower perioperative morbidity, reduced bleeding risk, and shorter hospital stay, with optimal outcomes observed in smaller stone burdens. Differences in efficacy between techniques were minimal for stones